A Review On Plant Derived Natural Products And Their Analogues With Chemoprotective Activity Against Genotoxicity Of Cyclophosphamide - SAI SAMPATH.T; KANAKA DURGA. M; SARANYA. BH; KALYANI.K (International Journal of Pharma and Bio Sciences, 2011)
Cyclophosphamide (CP), a common motherapeutic and immunosuppressive agent, is used in the treatment of wide range of cancers and autoimmune diseases. Besides that it is a well known carcinogen. The genotoxic potential limits its efficacy in the treatment of cancers. The present review was designed to ascertain the chemoprotective potential of natural products and their analogues on cyclophosphamide (CP) using bone marrow micronucleus test in mice, comet assay, chromosomal aberrations (CA) and sister chromatid exchanges (SCE) assay methods. The prevalence of micronuclei, the extent of lipid peroxidation, and the status of the antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) in both liver and serum of mice were used as intermediate biomarkers of chemoprotection.